Asymptotic model for the propagation of surface waves on a rotating magnetoelastic half-space - Mubaraki Ali M. (Demonstratio Mathematica)
This article is focused on deriving the approximate model for surface wave propagation on an elastic isotropic half-plane under the effects of the rotation and magnetic field along with the prescribed vertical and tangential face loads. The method of study depends on the slow time perturbation of the prevalent demonstration for the Rayleigh wave eigen solutions through harmonic functions. A perturbed pseudo-hyperbolic equation on the interface of the media is subsequently derived, governing the propagation of the surface wave. The established asymptotic formulation is tested by comparison with the exact secular equation. In the absence of the magnetic field, the specific value of Poisson’s ratio, ν=0.25ν =0.25, is highlighted, where the rotational effect vanishes at the leading order.